2014
DOI: 10.1055/s-0034-1394396
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Computer Reminder System for Laboratory Monitoring of Metabolic Syndrome in Schizophrenic Outpatients Using Second-generation Antipsychotics

Abstract: The percentage of QPVs in the intervention group was higher than the control group and the different metabolic risk of SGAs also influenced the performance of laboratory examinations. Further studies are needed to confirm the results of our studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…This is in contrast to a previous study, which showed that when clinical decision support to alert the need for metabolic monitoring was used, the odds were 3.51 times greater that clinicians would complete the recommended measurements compared to a control group [7]. Differences may be due to baseline adherence, which was only around 3% [7] compared to our baseline of 76.7% [21]. As Ontario Shores adopts and integrates other CPGs within the EMR (eg, dementia, depression), appropriate coordination and use of clinical decision support will be required to maintain patient safety and a patient-centered approach to care.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…This is in contrast to a previous study, which showed that when clinical decision support to alert the need for metabolic monitoring was used, the odds were 3.51 times greater that clinicians would complete the recommended measurements compared to a control group [7]. Differences may be due to baseline adherence, which was only around 3% [7] compared to our baseline of 76.7% [21]. As Ontario Shores adopts and integrates other CPGs within the EMR (eg, dementia, depression), appropriate coordination and use of clinical decision support will be required to maintain patient safety and a patient-centered approach to care.…”
Section: Discussioncontrasting
confidence: 89%
“…Adherence to metabolic monitoring, for example, only increased slightly from 76.7% in the month prior to CPG implementation to 81.6% at 1-year follow-up [21]. This is in contrast to a previous study, which showed that when clinical decision support to alert the need for metabolic monitoring was used, the odds were 3.51 times greater that clinicians would complete the recommended measurements compared to a control group [7]. Differences may be due to baseline adherence, which was only around 3% [7] compared to our baseline of 76.7% [21].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other tools, such as an automated messaging program, stopgap measures to require providers to complete certain tasks in the prescription and monitoring of neuroleptics, dissemination of educational resources and tools, or the use of monitoring checklists with neuroleptic use, can prove fruitful in improving monitoring of neuroleptics. 32 Patients treated with a neuroleptic medication with input from psychiatry were more likely to have monitoring completed. This is exemplified in Fig 1, in which we highlight the value of integrated psychiatric consultation within medical settings in a case within our study cohort in which psychiatric consultation had significant impacts on addressing diagnosis, management, and drug monitoring.…”
Section: Adesmentioning
confidence: 99%
“…Several quality improvement and randomized controlled studies have suggested improved screening rates in patients with SMI after using a variety of provider education, peer interventions, and reminder methods. [12][13][14][15] In contrast, patient-centered education for patients with SMI on metabolic monitoring does not improve adherence to monitoring parameters. 16…”
Section: Introductionmentioning
confidence: 96%